2017
DOI: 10.3390/molecules22122175
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of β-CD-Ellagic Acid Microspheres and Their Effects on HepG2 Cell Proliferation

Abstract: Objective: In this study, β-cyclodextrin (β-CD) was chosen as the coating for ellagic acid to prepare ellagic acid microspheres, and the effect of microspheres on the growth of HepG2 cells was observed. Methods: Scanning electron microscopy, infrared spectroscopy, and release rate analysis were used to identify the formation of ellagic acid microspheres. Methyl thiazolyl tetrazolium (MTT) assay was used to detect the effect of different concentrations of ellagic acid microspheres on tumor cell proliferation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The assay was conducted in accordance with the protocol described previously with slight modification [16]. Briefly, for saturated aqueous solution preparation, 5 g of β-CD was dissolved in 200 ml of double-distilled water (DDW).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay was conducted in accordance with the protocol described previously with slight modification [16]. Briefly, for saturated aqueous solution preparation, 5 g of β-CD was dissolved in 200 ml of double-distilled water (DDW).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, EA has a short plasma half-life because its oral administration leads to a lactone ring opening by the intestinal microorganism and is rapidly eliminated from the body, which are the main causes of its low bioavailability [15]. Therefore, the preparation of slow-release ellagic acid microspheres could solve these problems [16]. Nanoparticles (NPs) are considered to be the most promising delivery system for compounds with low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the encapsulation of ellagic acid to enhance its poor solubility combined with an improvement of its controlled delivery was attempted by some research groups [ 148 , 149 ]. In a recent work, Pirzadeh-Naeeni et al reported the nanoencapsulation of ellagic acid in two different biopolymers (schizophyllan and chitin), which were then tested against MCF-7 breast cancer cells [ 150 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…By following a different preparative procedure, β-CD was again chosen as EA complexing agent in another study [62]. A saturated aqueous β-CD solution was slowly mixed with 125 mg/mL of EA ethanolic solution and stirred for 2 h at rt, then the mixture was filtered and finally freezedried.…”
Section: Ea Inclusion In Cyclodextrins (Cd)mentioning
confidence: 99%